2020
DOI: 10.1038/s41598-020-71803-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonded host–guest systems are stable in ionic liquids

Abstract: We show that H-bonded host–guest systems associate in ionic liquids (ILs), pure salts with melting point below room temperature, in which dipole–dipole electrostatic interactions should be negligible in comparison with dipole-charge interactions. Binding constants (Ka) obtained from titrations of four H-bonded host–guest systems in two organic solvents and two ionic liquids yield smaller yet comparable Ka values in ionic liquids than in organic solvents. We also detect the association event using force spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…When embedded in a polymer matrix, it becomes difficult to directly measure changes in the association strength of these H-bond moieties, and only a few studies of changes in bonding strength in bulk polymers have been reported, [13,[19][20][21][22][23] mainly focusing on the impact of organic solvents. [24] We here report a systematic study on the influence of ionic liquids (ILs) on the association of the quadruple H-bonding motif UPy, by systematically embedding them into a microenvironment of increasing IL content. As the behavior of such UPy-system is crucial in the design of self-healing electrolytes or 3D-printing, [25] knowledge of their stability in ILs is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When embedded in a polymer matrix, it becomes difficult to directly measure changes in the association strength of these H-bond moieties, and only a few studies of changes in bonding strength in bulk polymers have been reported, [13,[19][20][21][22][23] mainly focusing on the impact of organic solvents. [24] We here report a systematic study on the influence of ionic liquids (ILs) on the association of the quadruple H-bonding motif UPy, by systematically embedding them into a microenvironment of increasing IL content. As the behavior of such UPy-system is crucial in the design of self-healing electrolytes or 3D-printing, [25] knowledge of their stability in ILs is important.…”
Section: Introductionmentioning
confidence: 99%
“…When embedded in a polymer matrix, it becomes difficult to directly measure changes in the association strength of these H‐bond moieties, and only a few studies of changes in bonding strength in bulk polymers have been reported, [ 13,19‐23 ] mainly focusing on the impact of organic solvents. [ 24 ]…”
Section: Introductionmentioning
confidence: 99%
“…It was not until the second half of the twentieth century that interest in the subject area increased, catalysed by the potential use of ionic liquid as solvents in electrochemical applications 5 . The areas to which ionic liquid have been directed have expanded, particularly since the development of air stable ionic liquids 5 , to include rather diverse fields from chemistry (including cellulose processing 6 , gas capture 7 , synthesis 8 and understanding the nature of hydrogen bonding 9 ) to more machine industry targeted applications, such as tribology 10 .…”
Section: Introductionmentioning
confidence: 99%
“…It was not until the second half of the 20th century that interest in the subject area increased, catalyzed by the potential use of ionic liquid as solvents in electrochemical applications. 5 The areas to which ionic liquid have been directed have expanded, particularly since the development of air stable ionic liquids, 5 to include rather diverse elds from chemistry (including cellulose processing, 6 gas capture, 7 synthesis 8 and understanding the nature of hydrogen bonding 9 ) to more machine industry targeted applications, such as tribology. 10 The changing technological landscape, with the rapid shift towards vehicle electri cation and green energy production being the obvious examples, along with environmental concerns, has resulted in a need for lubricants with enhanced functionality such as electrical responsivity.…”
Section: Introductionmentioning
confidence: 99%